The The Implementation of Accounting Standard for MSMEs: The Effect of Perception Accounting Understanding and Socialization - Deni Hamdani; Ferry Kosadi; Diah Febriyanti (Institut Bisnis dan Informatika Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to the national economy and possess substantial opportunities for ongoing development. Nonetheless, inadequate financial literacy hampers the creation of standardized financial records. This research aims to examine the execution of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and the effect of MSME participants' perceptions, accounting knowledge, and socialization on its execution. A quantitative method was applied utilizing descriptive and verification techniques. The study population included MSME participants from the handicraft sector registered with the Bandung City Cooperatives and MSMEs Office, with samples acquired proportionally using the Slovin formula. The research results indicate that MSME actors' perceptions do not have a significant effect on SAK EMKM implementation, accounting knowledge plays a substantial role, the socialization of SAK EMKM significantly influences it, and accounting knowledge and socialization collectively affect the implementation of SAK EMKM. In conclusion, increasing awareness and social interaction is crucial in encouraging the adoption of SAK EMKM to improve MSME financial literacy.